2014
DOI: 10.1007/s11356-014-3805-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of behavioural assays using zebrafish larvae to assess neurotoxicity

Abstract: Testing of compounds for neurotoxicity has become increasingly important in recent years. It has been shown that neurological disorders like autism may be related to chemical exposures, which may play a crucial role in the progression of these diseases. Special attention has been be given to the substances causing developmental neurotoxicity as the developing nervous system is more vulnerable to impacts by chemicals than the adult nervous system. The zebrafish (Danio rerio) is a well-established model species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 56 publications
(67 reference statements)
0
61
0
Order By: Relevance
“…This seems certain for ethanol and paracetamol, since their human cardiotoxic impact is observed as a late effect after drug poisoning. In fact, paracetamol has been reported to have no impact on the heart rate in zebrafish larvae [50,57], to the point that Wen et al [54] included this drug as a negative cardiotoxic drug [57]. In summary, we support zebrafish as a powerful tool for predicting drug-induced cardiotoxic liabilities in humans, including typical repolarization and depolarization end-phenotypes such as QTc or EJC.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This seems certain for ethanol and paracetamol, since their human cardiotoxic impact is observed as a late effect after drug poisoning. In fact, paracetamol has been reported to have no impact on the heart rate in zebrafish larvae [50,57], to the point that Wen et al [54] included this drug as a negative cardiotoxic drug [57]. In summary, we support zebrafish as a powerful tool for predicting drug-induced cardiotoxic liabilities in humans, including typical repolarization and depolarization end-phenotypes such as QTc or EJC.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have shown the relevance of using zebrafish for predicting the possible impact of drugs in those three organs individually [21,29,50,51,52,53,54,55,56]. However, no previous studies have integrated the analysis of these three organ-toxicities in the same animal; a procedure that reduces animal usage, experimental time and costs, and the quantity of the tested compound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many features of zebrafish (Danio rerio) have made it become a model system for the examination of environmental toxicology [14]. It also help to determine the critical neuro-developmental processes impacted by organophosphorus pesticides, Chlorpyrifos as an instance [10,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral profiling in zebrafish has elucidated diverse mechanisms of action [7,8]. There are various behavioral tests that can be performed on developing zebrafish, however, these complex phenotypes introduce many analytical challenges [9,10]. Recent reviews have evaluated currently available statistical methods, including traditional methods such as Student’s T test and analysis of variance (ANOVA), as well as more advanced methods such as behavioral barcoding, multivariate analysis of variance (MANOVA), and pattern matching methods, in addressing different behavioral tests of developing zebrafish [7,8,10,11].…”
Section: Introductionmentioning
confidence: 99%